Dynamics of magnetic flux propagation in bulk, single grain superconducting rings during pulsed field magnetisation. (1st November 2022) - Beck, Michael; Tsui, Yee Kin; Shi, Yun Hua; Moseley, Dominic; Dennis, Anthony R; Cardwell, David A; Durrell, John H; Ainslie, Mark D
Abstract: When used as trapped field magnets (TFMs), single grain, bulk high-temperature superconducting (HTS) rings are promising candidates for the generation of strong, uniform magnetic fields for nuclear magnetic resonance. The pulsed field magnetisation (PFM) technique provides a low cost, compact and portable method to magnetise these samples as TFMs; however it has proven difficult to achieve high trapped fields in HTS rings using PFM. To date, a record field of only 0.60 T has been achieved for rings magnetised by single-pulse PFM—compared with over 4 T for disc-shaped HTS—and the reasons for this discrepancy are poorly understood. In this work, we use the finite element method to model the propagation of magnetic flux into HTS rings under quasi-static zero field cooled magnetisation and PFM, and validate the results analytically and experimentally. Magnetic flux is found to penetrate finite HTS rings from both the inner and outer surfaces, inducing a negative field at the inner face of the ring. This field is reversed as the applied field increases past the point of full penetration, locally dissipating magnetic energy and heating the sample. HTS rings are therefore more susceptible to local instabilities that severely limit their ability to trap a useful magnetic field. Consequently, thermomagnetic stability of HTS rings during single-pulse PFM can only be ensured by taking careful consideration of reducing flux movement through the bulk around the point at which the field is reversed. This may require more advanced PFM techniques like waveform control or multi-pulse stepwise-cooling to reduce local heating and increase the trapped field.